Analisis Kesalahan Berbahasa Tataran Sintaksis Dalam Tajuk Surat Kabar Republika - Saraswati, Wahyu Diyah; Hermaliza, Hermaliza (UIR PRESS, 2021)
Newspapers are media of information read by the public. Thus, the use of language has an important role in making newspapers, especially journalism, so that language errors do not occur. However, language errors were still found in the headline of the Republika newspaper at the syntactic level in the field of phrases and sentences. This language error occurs because of a lack of understanding of the rules of the Indonesian language in writing news. The problems in this research are 1. How is the language error at the syntactic level of the phrase field in the headline of the Republika newspaper? 2. How is the language error at the syntactic level of the sentence field in the headline of the Republika newspaper? The purpose of this research is to describe, classify and analyze language errors at the syntactic level of the phrases and sentences in the headline of the Republika newspaper in order to obtain actual results. This type of research is qualitative research with descriptive methods. The data in this study are language errors in the fields of phrases and sentences contained in the headline of the Republika newspaper. The theory used refers to various theories put forward by Setyawati (2010) and Tarigan (2011). Techniques for data collection using documentation and Content Analysis (Content Analysis). The results of data analysis that has been carried out in the Headline of the Republika newspaper, found 36 errors in the phrase field, namely the influence of regional languages, the use of inappropriateprepositions, the use of excessive or redundant elements and excessive superlative forms. The sentence field errors found 84 errors, namely sentences that are not subject to, sentences are not subject to and are not predicated (stumped sentences), omission of conjunctions, excessive use of conjunctions, using foreign terms and using unnecessary question words. So there were 120 errors in the language at the syntactic level in the Header of the Republika newspaper.